Analisis Yuridis Pengaturan Pelintasan Jalan untuk Pengangkutan Hasil Tambang - Kurdi, Kurdi; Mazjah, Ibnu; Cahayo, Raul Gindo (Fakultas Hukum Universitas Islam Jember, 2025)
One of the districts in Aceh Province that has quite high potential mineral and coal reserves is West Aceh District. One of the companies holding a Coal Commodity IUP in Aceh is PT. Mifa Bersaudara. In the process of transporting West stone mining results from PT Mifa, there is an alleged crossing of the Regency road which occurred due to an overlap between the Regency road area and the IUP mining area. The alleged crossing of the Balee-Reudeup road which is included in the Regency road by PT Mifa raises questions regarding the authority to manage the Regency road that crosses the IUP area. This study is intended to determine the condition of the road crossing rules for transporting mining results in the applicable laws and regulations and the application of these regulations in the case of crossing the West Aceh Regency road by PT Mifa Saudara. The results of the study indicate that the road crossing rules for transporting mining results in West Aceh are still ineffective because they cannot force companies to have a road crossing permit, including in resolving the case of crossing the Balee-Reudeup road without a permit by PT Mifa Bersaudara. This ineffectiveness is evident from the absence of regulations to reimburse the losses experienced by the West Aceh Regional Government due to road damage caused by unauthorized road crossings. ABSTRAK Salah satu kabupaten di Provinsi Aceh yang memiliki potensi cadangan mineral dan batubara cukup tinggi adalah Kabupaten Aceh Barat. Salah satu perusahaan pemegang IUP Komoditas batubara di Aceh yakni PT. Mifa Bersaudara. Pada proses pengangkutan hasil tambang batu Barat PT Mifa, terdapat dugaan crossing jalan Kabupaten yang terjadi akibat adanya tumpang tindih antara wilayah jalan kabupaten dengan wilayah IUP tambang. Dugaan crossing jalan Balee-Reudeup yang termasuk dalam jalan Kabupaten oleh PT Mifa tersebut menimbulkan pertanyaan terkait kewenangan pengelolaan jalan Kabupaten yang melintasi area IUP. Penelitian ini dimaksudkan untuk mengetahui kondisi aturan perlintasan (crossing) jalan untuk mengangkut hasil tambang dalam peraturan perundang-undangan yang berlaku dan penerapan pengaturan tersebut dalam kasus crossing jalan Kab. Aceh Barat oleh PT Mifa bersaudara. Hasil penelitian menunjukkan bahwa aturan pelintasan (crossing) jalan untuk pengangkutan hasil tambang di Aceh Barat masih belum efektif karena tidak dapat memaksa perusahaan memiliki izin pelintasan (crossing) jalan, termasuk dalam penyelesaian kasus crossing jalan Balee-Reudeup tanpa izin oleh PT Mifa Bersaudara. Ketidakefektifan ini terlihat dengan ketiadaan aturan untuk mengembalikan kerugian yang dialami Pemda Aceh Barat akibat kerusakan jalan yang terjadi akibat crossing jalan tanpa izin. Kata Kunci: Crossing Kalan; Perizinan; Pertambangan; Aceh Barat